Microencapsulação de Lactobacillus plantarum BG 112 com Acrycoat ® S100 para aplicação como probiótico em salame - Vasconcelos, Lia Inês Machado (2016)
L. plantarum has come to stand out as a promising microorganism for use in food matrices with health promotion purposes. However, due to their instability to external agents (oxygen, pH and temperature), their use in foods is compromised. Therefore, microencapsulation is a viable alternative for your application. The purpose of this work was to optimize the encapsulation of Lactobacillus plantarum BG112 with a methacrylic acid copolymer (Acrycoat® S100) by spray drying, perform the characterization of the obtained microcapsules and apply the microorganisms in meat product – milano type salami. For optimization, a Central Composite Rotatable Desing (CCRD) of type 22 with two independent variables, the encapsulated L. plantarum (% m.v-1) and encapsulating agent Acrycoat® S100 (% m.v-1) having as dependent variable Yield (%ER) and Efficiency (%EE) encapsulation of L. plantarum, totalizing 11 experiments with four factorial points, four axial points and triplicate at the central point. The characteristics and stability of the microcapsules were estimated by analises: culture of viable cell count, microscopy analysis, moisture, water activity, hygroscopicity, Differential Scanning Calorimetry (DSC), Thermogravimetry (TGA) and Infrared Spectroscopy Fourier Transform (FTIR – UATR). In the CCRD, the maximum obtained value of %ER was 39.3% and %EE was 86.8%, values near the central point of the region where in both answers were influenced significantly (p<0.05) the variables under study. It considered the response efficiency as the main parameter to the probiotic effect the proposed product, thus setting up the optimal surface. It was applied the L. plantarum microencapsulated in type salami Milano comparing it to a control with commercial starter culture. The curve of pH and weight loss during ripening, chemical-physical and microbiological qualities were evaluated. Both revealed the absence of Salmonella spp. and low levels in Staphylococcus coagulase positive count, coliforms at 45 °C and Clostridium sulphite reducing to 46 °C and is suitable for consumption. Regarding to total lactic acid bactéria, the concentration was against the current legislation to characterize the final product as functional (108 CFU.g-1). Following samples were evaluated by 141 consumers by hedonic scale test, no significant difference (p>0.05) showed for the evaluated attributes (color, aroma, texture, taste, overall acceptance and purchase intent). So The data demonstrated the ability of Acrycoat® S100 as a support material for the microencapsulation of probiotics, allowing develop a fermented Milano salami formulation L. plantarum. The proposed product was stable in relation to pH. It was in accordance with the physico-chemical parameters and microbiological of current legislation, accepted sensorially. Besides reach amount of lactic acid bacteria at the minimum level required by Brazilian law for functional foods.